2008
DOI: 10.1242/jcs.020081
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 alters Ca2+ signal duration through specific interaction with the Gαq family of G proteins

Abstract: Caveolae are membrane domains having caveolin-1 (Cav1) as their main structural component. Here, we determined whether Cav1 affects Ca2+ signaling through the Gαq–phospholipase-Cβ (PLCβ) pathway using Fischer rat thyroid cells that lack Cav1 (FRTcav–) and a sister line that forms caveolae-like domains due to stable transfection with Cav1 (FRTcav+). In the resting state, we found that eCFP-Gβγ and Gαq-eYFP are similarly associated in both cell lines by Forster resonance energy transfer (FRET). Upon stimulation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
59
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 63 publications
6
59
0
Order By: Relevance
“…Once activated by receptors, G␣ q subunits stimulate PLC␤, which catalyzes the hydrolysis of phosphatidylinositol 4,5-bisphosphate leading to Ca 2ϩ release from intracellular stores (6,7). Based on previous work (8,9), we found that Cav-1 or -3 specifically binds G␣ q , and the affinity between the two proteins increases when G␣ q is activated (4). The stabilization of activated G␣ q by Cav1/3, coupled with release of G␤␥ from caveola domains during the activation cycle, has the net effect of prolonging PLC␤ activation and increasing the extent and duration of Ca 2ϩ responses.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…Once activated by receptors, G␣ q subunits stimulate PLC␤, which catalyzes the hydrolysis of phosphatidylinositol 4,5-bisphosphate leading to Ca 2ϩ release from intracellular stores (6,7). Based on previous work (8,9), we found that Cav-1 or -3 specifically binds G␣ q , and the affinity between the two proteins increases when G␣ q is activated (4). The stabilization of activated G␣ q by Cav1/3, coupled with release of G␤␥ from caveola domains during the activation cycle, has the net effect of prolonging PLC␤ activation and increasing the extent and duration of Ca 2ϩ responses.…”
mentioning
confidence: 70%
“…Our laboratory has shown that the presence of caveolae directly affects Ca 2ϩ signals mediated through the G␣ q /phospholipase C␤ (PLC␤) 2 pathway (4,5). Receptors that activate this pathway bind dopamine, acetylcholine, bradykinin, and angiotensin II as well as other hormones and neurotransmitters.…”
mentioning
confidence: 99%
“…Previously, Escribá et al showed that PE enhances the binding of Gα-subunit to model membranes (45). FRET experiments using X-rhodamine isothiocyanate (XRITC)-Gα q -subunit, XRITC-Gβγ-subunit, and caveolin-1 (Cav1)-EGFP showed that Gα q -subunit has a stronger affinity for Cav1-EGFP than Gβγ-subunit has (46). Our results, together with results of others, suggest that PE provides a platform for PLCβ1 activation by sensing curved membranes, such as caveolae, via the C-terminal domains.…”
Section: Discussionmentioning
confidence: 99%
“…Although PLC1 is concentrated at the cell membrane, it is also present throughout the cell, whereas G q is more-or-less membrane specific, where it stably associates with PLC1 to allow for rapid transmission of intracellular signals via GPCRs such as the M3 muscarinic receptor (Dowal et al, 2006). Recent evidence suggests that caveolin-1 can have a regulatory role, promoting dissociation of G subunits from  subunits to facilitate GPCR signal transduction (Sengupta et al, 2008). Interaction between caveolin-1 and -dystroglycan appears to be necessary for such a functional role, because in human airway smooth muscle cells with stably silenced -dystroglycan, PLC1 and G q were lost from caveolae and accumulated in fractions that are typically devoid of caveolae.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these results support a role for the actin cytoskeleton, through its tethering to a DGC-caveolin-1 complex, in the establishment and maintenance of discrete caveolae microdomains in smooth muscle cells. release in the smooth muscle and other cell systems (Daniel et al, 2009;Darby et al, 2000;El-Yazbi et al, 2008;Gosens et al, 2007b;Prakash et al, 2007;Sengupta et al, 2008;Zhu et al, 2008). We assessed whether this functional role is linked to the unique ordered distribution of caveolae in contractile smooth muscle cells.…”
Section: The Actin Cytoskeleton Underpins the Ordered Distribution Ofmentioning
confidence: 99%